2018
DOI: 10.2478/folmed-2018-0001
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Aluminum Phosphide Poisoning: Case Report and Current Management

Abstract: Aluminum phosphide (AlP) is a commonly used cheap rodenticide, insecticide, and fumigant. Most intoxications in the literature are suicidal ingestions, however, AlP may cause incidental inhalational toxicities as well. After ingestion or inhalation, nausea, vomiting, dyspnea and abdominal pain develops within minutes. Hallmark of toxicity is refractory hypotension, cardiac failure and severe metabolic acidosis developing within a matter of hours are the major cause of mortality. In Turkey, AlP tablets are wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 12 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…Phosphine gas blocks cytochrome C oxidase in the mitochondria leading to disruption of oxygen transport in the electron transport chain causing cell death. It also releases reactive oxygen species (superoxide and hydrogen peroxide) that causes lipid peroxidation and cell death [7]. Some studies suggested the use of Glutathione, Vit C and E, Carotenes, and melatonin helps in reducing the oxidative stress in cases of ALP poisoning and hence better prognosis [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphine gas blocks cytochrome C oxidase in the mitochondria leading to disruption of oxygen transport in the electron transport chain causing cell death. It also releases reactive oxygen species (superoxide and hydrogen peroxide) that causes lipid peroxidation and cell death [7]. Some studies suggested the use of Glutathione, Vit C and E, Carotenes, and melatonin helps in reducing the oxidative stress in cases of ALP poisoning and hence better prognosis [8].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is mainly clinical with positive history of ALP tablets ingestion, garlic odor at presentation, and symptoms suggestive of ALP ingestion. However, silver nitrate test on gastric aspirate and gas chromatography with a nitrogenphosphorus detector can be done for diagnosis in case of doubt [7,8]. There is no specific antidote available for ALP poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of rice tablet toxicity includes cytochrome C oxidase inhibition by phosphine gas, oxidative injury, and lipid peroxidation that cause cellular injury. [ 6 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although aluminum phosphide poisoning is commonly seen in fumigation and via an oral route through wheat-pill ingestion, our patient accidentally got exposed to the poison while working in a damp, unaerated wheat storage unit. Our review of articles showed only one such reported case [4]. Through this article, we would like to bring to attention this rare mode of poisoning so that timely measures can be taken to avoid an unfavorable outcome, as studies have shown that timely intervention can save lives [5] especially in inhalational poisoning of aluminum phosphide [4].…”
Section: Discussionmentioning
confidence: 99%
“…Although cases of orally ingested wheat pills for suicide and poisoning by fumigation are prevalent [1], we hereby discuss the case of wheat-pill poisoning due to inhalation in a closed space. In an extensive review of literature on PubMed using the keywords “wheat pill,” “aluminum phosphide” and “poisoning,” we could find only one reported case of poisoning by aluminum phosphide due to inhalation in a closed space [4]. The objective of this article is to inform physicians about this unique mode of poisoning so that timely and appropriate management can be commenced to avoid an unfavorable outcome [5].…”
Section: Introductionmentioning
confidence: 99%